Guiana and the Shadows of Empire: Colonial and Cultural Negotiations at the Edge of the World - Hyles, Joshua R. (Lexington Books, 2013)
This book is a history of the three Guianas, now known as Guyana, Suriname, and French Guiana. Though histories of each of the countries exist, this is the first work in a century to consider the three countries as a group, and thus the first to present the history of all three as a comparative and overarching study. Special emphasis has been given to the story of how each colony was administered by Britain, the Netherlands, and France respectively, and how these differing colonial administrative policies have given rise to three vastly different cultures. Because the geographical area of the Guianas is relatively small, the indigenous population at the time of contact was relatively uniform across the area, and the external pressures on the three colonies over their histories exhibited significant similarities, the book presents the Guianas as an ideal laboratory in which to study the effects of imperialism and cultural assimilation practices. The book also briefly considers the present political and cultural status of the three polities and makes some projections about their possible futures. In all, the book presents a complete history from prehistory until the present day covering the entirety of the Guianas region, relating a colorful history from a little-studied corner of the world.